PENGARUH KEPUASAN KERJA, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DINAS TENAGA KERJA KABUPATEN JOMBANG JAWA TIMUR - Itsna Halimatur Rahma; Hadi Sunaryo; Muhammad Khoirul (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTThis study aims to analyze the effect of job satisfaction, motivation and workenvironment on employee performance. Questionnaires are used as an insrument for obtainingdata. The analysis tool used is SPSS with multiple linear regression approach. The object ofthis research is Employee of Manpower Office of Jombang Regency, with population of 30Employees. Based on multiple linear regression test, job satisfaction variable has an effect onemployee performance variable. Variable of motivation have an effect on employeeperformance variable. And work environment variables on employee performance. From theresults of this study to increase the promotion given to all employees by way of employeesknow all the promotional requirements provided by superiors to establish an openness with soall employees have the same rights to pursue the campaign. The fulfillment of individualactualization of each employee has not been fulfilled well to improve it by the fulfillment of allthe quality and capacity owned by every employee of the workforce of Jombang regency, theworking atmosphere of the employees has not fully able to concentrate well on the noisesituation that exist in the environment where they work because the location of the serviceLabor is in the middle of the city.Keywords: Job satisfaction, Motivation, Work environment, and Employee Performance.